Design of piezoelectric ocean-wave energy harvester using sway movement - Hwang, Won Seop; Ahn, Jung Hwan; Jeong, Se Yeong; Jung, Hyun Jun; Hong, Seong Kwang; Choi, Jae Yoon; Cho, Jae Yong; Kim, Jung Hun; Sung, Tae Hyun (Sensors and actuators. A. Physical., 2017)
•We design a piezoelectric ocean-wave energy harvester (POEH) that can harness wave energy.•The POEH uses a ball-and-rail mechanism to induce cantilever vibrations.•The POEH yields improved voltage and power output than cantilever system.•Our device can be used for low-frequency energy harvesting applications. The use of energy harvesting technologies for supplying power generating energy to wireless devices and sensors, particularly in scenarios where it is difficult to exchange or recharge batteries, has recently attracted considerable research attention. In this context, we report the design of a piezoelectric energy harvesting system that can be used to harvest energy from the ocean. The harvester is composed of a piezoelectric cantilever structure and a magnet as the tip-mass of the piezoelectric module, atop which a rail (tube) with a metal ball is positioned. The system is tested with a setup that simulates ocean waves. Our findings indicate that our approach can be utilized in the design of multipurpose piezoelectric energy harvesting systems for low frequency vibration and in “sea-based” applications involving buoys and boats.